ADVANCEMENTS IN MODERN SURGICAL MANAGEMENT OF TIBIAL PLATEAU FRACTURES: A COMPREHENSIVE REVIEW - Norin Forna; Paul-Dan Sîrbu; Savin Liliana; Lucian Eva; Wilhelm Friedl; Eugen Carata; Tudor Pinteală; Răzvan Tudor; Mihnea Theodor Sîrbu (Romanian Journal of Oral Rehabilitation)
This review aims to summarize the literature on classic and advanced surgical management strategies for tibial plateau fractures. The primary objective in treating these fractures is to restore joint functionality and ensure favorable short- and long-term outcomes. Effective surgical management minimizes the risk of joint instability, enhances long-term prognosis, and maintains the patient’s quality of life. Most orthopedic surgeons adopt a staged treatment strategy, involving initial stabilization followed by definitive surgical fixation, respecting soft tissue conditions, achieving precise anatomical reduction, ensuring stable fixation, and promoting early rehabilitation. Surgical techniques include open approaches with arthrotomy for articular surface reconstruction and fixation using plates and screws, as well as minimally invasive approaches such as arthroscopy or percutaneous fixation with screws or external fixators. Modern osteosynthesis techniques—plates, screws, external fixators, and rotating hinges—have become the standard of care, except in cases of minimal displacement. These approaches collectively aim to optimize patient recovery and joint functionality.